2018
DOI: 10.1007/s12253-018-0429-1
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of PhospholipaseD2 Induced by Hypoxia Promotes Proliferation of Colon Cancer Cells through Activating NF- κ Bp65 Signaling Pathway

Abstract: Hypoxia is a typical feature of colon cancer occurrence and progression. We have reported that high expression and activity of PhospholipaseD2 (PLD2) induced by hypoxia in colon cancer cells. In order to further investigate the role of PLD2 in colon cancer under hypoxic conditions. MTT assay was used to detect the proliferation of human colon cancer cells (SW480 and SW620) under hypoxic conditions by decrease the PLD2 gene expression or inhibit the activity of PLD2. Expression level of p-P65/T-P65 and Cyclin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
4
12
0
Order By: Relevance
“…In our study, we found that lipid metabolism was significantly down-regulated in HR-MUT. Beyond our own results, other studies have confirmed that lipid metabolism rearrangement is involved in the regulation of the CRC cell chemotherapy resistance mechanism ( Fiucci et al, 2000 ; Cotte et al, 2018 ), plays a role in the occurrence and development of CRC ( Hwang et al, 2014 ; Liu et al, 2016 ; Mihajlovic et al, 2019 ; Liu et al, 2020 ), and has an impact on the prognosis ( de Figueiredo Junior et al, 2018 ). Research has also found that lipid droplets (LD) levels in CRC cells are significantly higher than in those of normal cells, indicating that it may play a key role in the development of CRC ( Accioly et al, 2008 ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In our study, we found that lipid metabolism was significantly down-regulated in HR-MUT. Beyond our own results, other studies have confirmed that lipid metabolism rearrangement is involved in the regulation of the CRC cell chemotherapy resistance mechanism ( Fiucci et al, 2000 ; Cotte et al, 2018 ), plays a role in the occurrence and development of CRC ( Hwang et al, 2014 ; Liu et al, 2016 ; Mihajlovic et al, 2019 ; Liu et al, 2020 ), and has an impact on the prognosis ( de Figueiredo Junior et al, 2018 ). Research has also found that lipid droplets (LD) levels in CRC cells are significantly higher than in those of normal cells, indicating that it may play a key role in the development of CRC ( Accioly et al, 2008 ).…”
Section: Discussionsupporting
confidence: 53%
“…Research has also found that lipid droplets (LD) levels in CRC cells are significantly higher than in those of normal cells, indicating that it may play a key role in the development of CRC ( Accioly et al, 2008 ). Many studies have confirmed that lipid metabolism-related enzymes participate in the occurrence and development of CRC ( Liu et al, 2020 ), regulate cell proliferation and invasion ( Sánchez-Martínez et al, 2015 ; Nath and Chan, 2016 ), and participate in drug resistance ( Fiucci et al, 2000 ; Cotte et al, 2018 ). Because of this, fatty acids, phospholipids, and cholesterol are synthesized actively, and their concentrations are significantly increased in tumor tissues ( Janardhan et al, 2006 ; Lupu and Menendez, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…PLD2 is one of the two isoforms of PLD in mammals, which catalyzes the hydrolysis of the diester bond of phospholipids to generate PA and the free lipid headgroup (39). PLD2 expression is elevated in a number of human tumors and is highly variable (16,(19)(20)(21)(22). In CRC, the expression level of PLD2 was significantly associated with tumor size and survival of patients, which suggests that PLD2 may be a target for therapy in CRC (40).…”
Section: Discussionmentioning
confidence: 99%
“…A total of two mammalian isoforms of PLD have been described; PLD1 and PLD2, which are almost ubiquitous and share ~50% homology (17,18). PLD2 overexpression increases proliferation, adhesion, invasion and metastasis in a wide variety of cancers including gastric, colorectal, renal, stomach, lung and breast cancers (16,(19)(20)(21)(22). In addition, it has been reported that PLD2 is associated with multidrug resistance in human cancer cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…After phosphorylation, p65 binds to p50 to form a heterodimer and is transferred to the nucleus to initiate downstream gene transcription. Studies have shown that aberrantly activated p65 (RelA) contributes to tumor development and progression [19,20]. In addition, the existence of co-immunoprecipitation between p65 and ACTN4 in non-small lung carcinoma cells has been reported [21].…”
Section: Introductionmentioning
confidence: 99%